Effect of short-term coaching program to enhance basketball technical skills of passing, shooting, and dribbling - Ji, Xueyan; Samsudin, Shamsulariffin; Yuan, Yubin; Mohd Nasiruddin, Nasnoor Juzaily; Farizan, Noor Hamzani; Chee, Chen Soon (University of the Balearic Islands, 2023)
Basketball's physical demands and wide appeal make numerous societal applications feasible. Through a short-term physical and psychological exercise program, this study sought to improve collegiate basketball players' physical, psychological, and technical skills during their off-study period. Twenty-four university basketball players older than 18 and in good physical and mental health participated in the study. Twelve participants were assigned to the experimental group and twelve to the control group. The instruction program lasted three weeks and consisted of four two-hour weekly sessions. The experimental group received specialized instruction in shooting, passing, and dribbling. In contrast, both groups received training in fundamental skills, aerobic fitness, vertical jumping, arm and trunk muscle endurance, and rudimentary playing skills. The study's results revealed that both unique and mixed training improved maximal oxygen uptake, with both groups experiencing similar improvements. Aerobic fitness and strength improved roughly 30 in the specific training group and 20 in the combined training group. Moreover, performance in three basketball technical skills increased by 17 to 27 in both groups, with a tendency for shooting and passing skills to develop more significantly in the training group. These results suggest that an exclusively on-court basketball training program (special training) is as effective as a combined training program at enhancing aerobic and anaerobic fitness. Based on the provided fit indices, the adaptability of the green enterprise model to basketball players demonstrates an acceptable and decent fit. The findings emphasize the potential for targeted and specific training to improve basketball players' physical and technical abilities during their off-season.